Benchmarking the Integration of Corridors in International Value Networks: The Study of African Cases - (:unkn) unknown (My University, 2016)
In December 2008, the African Development Bank (AfDB) announced that its discussions with the Libyan authority surrounding the African integration process were advancing well.1 The construction of a highway between the Libyan border and southern Niger, one of the major projects proposed to achieve integration, is believed to hold considerable potential by Muammar Qaddafi, the Leader of the Libyan Jamahiriya. Considering Qaddafi's position on the creation of the United States of Africa, corridor development plans suddenly become pragmatic continental integration tools capable of federating Nations. After all, is that not one of the structuring effects of the construction of railroads in North America during the nineteenth century? In the African case, the political outcomes of this can only be speculative, but for stakeholders of economic development in SubSaharan Africa (SSA), these plans foster many expectations. © 2011 Peter Hall, Robert J. McCalla, Claude Comtois and Brian Slack.
Keywords: African Research